THE ROLE OF JNK IN THE PROINFLAMMATORY ACTION OF THE SARS-CoV-2 PROTEIN ORF3a - Aranđelović, Lena (Medicinski podmladak, 2025)
Introduction: Coronavirus disease 2019 (COVID-19) is a contagious respiratory infection caused by the novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). A significant contributor to the pathogenesis of COVID-19 is the SARS-CoV-2 regulatory protein open reading frame 3a (ORF3a), which drives an excessive inflammatory response associated with adverse clinical outcomes and mortality. Notably, c-Jun N-terminal kinase (JNK), a part of the mitogen-activated protein kinase (MAPK) family, is essential in orchestrating the cellular innate and adaptive immune response initiated by diverse viral infections. Aim: This study aims to elucidate the involvement of JNK in the proinflammatory response induced by SARS-CoV-2 ORF3a in the H460 non-small cell lung cancer cell line, specifically focusing on the expression of proinflammatory cytokines IL-1β and IL-8. Material and Methods: The H460 cell line was transfected with a DNA plasmid encoding the SARS-CoV-2 ORF3a. Pharmacological inhibition of JNK in H460 cells was achieved using JNK inhibitor SP600215. The expression of p-JNK and JNK was confirmed by immunoblotting, while RT-qPCR was used to quantify IL-1β and IL-8 mRNA levels. Student's t-test was used for statistical analysis.Results: H460 cells expressing SARS-CoV-2 ORF3a displayed a significant increase in JNK phosphorylation and IL-1β and IL-8 mRNA levels, as verified by immunoblot analysis and RT-qPCR respectively (p
Keywords: COVID-19; SARS-CoV-2; proinflammatory cytokines; ORF3a; JNK